Investigating Systemic Metabolic Effects of Betula alba Leaf Extract in Rats via Urinary Metabolomics - Gregorio Peron; Alina Yerkassymova; Gokhan Zengin; Stefano Dall’Acqua (Metabolites)
Background/Objectives: Herbal extracts from Betula alba (birch) are traditionally used for their purported diuretic effects, but scientific evidence supporting these claims remains limited. In this pilot study, we evaluated the short-term effects of a standardized B. alba leaf extract in healthy adult rats using an untargeted urinary metabolomics approach based on UPLC-QTOF. Methods: Two doses, 25 or 50 mg/kg, of a standardized B. alba extract were orally administered to rats. The extract contains hyperoside (0.53%), quercetin glucuronide (0.36%), myricetin glucoside (0.32%), and chlorogenic acid (0.28%) as its main constituents. After 3 days of treatment, the 24 h urine output was measured. Results: While no statistically significant changes were observed in the 24 h urine volume or the urinary Na+ and K+ excretion, multivariate metabolomic analysis revealed treatment-induced alterations in the urinary metabolic profile. Notably, the levels of two glucocorticoids, i.e., corticosterone and 11-dehydrocorticosterone, were increased in treated animals, suggesting that the extract may influence corticosteroid metabolism or excretion, potentially impacting antidiuretic hormone signaling. Elevated bile-related compounds, including bile acids and bilin, and glucuronidated metabolites were also observed, indicating changes in bile acid metabolism, hepatic detoxification, and possibly gut microbiota activity. Conclusions: Although this study did not confirm a diuretic effect of B. alba extract, the observed metabolic shifts suggest broader systemic bioactivities that warrant further investigation. Overall, the results indicate that the approach based on urinary metabolomics may be valuable in uncovering the mechanisms of action and evaluating the bioactivity of herbal extracts with purported diuretic properties.